Analysis of mesothelioma cases and National Cancer Registry data to assess asbestos exposure in India - R. Singh; A. L. Frank (The Union, 2024)
SETTING: Asbestos exposure can cause mesothelioma, a form of cancer which should be recorded by cancer registries. However, such registries currently cover only a small fraction (16%) of the population in India. Because India still uses asbestos, it is important to understand its health impact, especially the number of mesothelioma cases. OBJECTIVE: To assess the number of mesothelioma cases in India and compare these to the number reported to the National Cancer Registry. DESIGN: We used the Right to Information Act 2005 to gather data for 83 hospitals across India from 2012 to 2022-2023. RESULTS: From a total of 83 hospitals, there were 2,213 cases of mesothelioma from 2012 onwards. During the 2012-2016 period, the number of reported cases in the Cancer Registry was 54, whereas 1,126 cases were reported by these hospitals for this period. Only 21 (25%) of the hospitals assessed in this study were part of the population-based national cancer registry programme. Overall, cases of mesothelioma occur far more frequently than are reported in cancer registries. CONCLUSION: National record-keeping is inadequate and the system needs to be expanded and improved across all of India. This will provide more effective reporting and help to highlight the risk of exposure to asbestos.